Mission accomplished (Perwira Niaga Malaysia, 2015)
The Journey of Military General Tan Sri (Dr) Mohamed Hashim bin Mohd Ali (Rtd) from Soldier to Leader was published by PERNAMA as a token of appreciation for his contributions as PERNAMA chairman from 1992 to 2013. The book contains 134 pages with photos from his personal collection, chronology of life throughout his career in the army, and experience in leading the Armed Forces from 1954 to 1992. His involvement in the military began at the Federal Military College, Port Dickson in 1954 before leaving for Eaton Hall Cadet School in Chester in 1955 and The Royal Military Academy Sandhurst, the British Army Training Academy for Young Officers during the 18th intake. His four-decade career began at the Armed Forces during the early years of Malaya's independence, witnessing the establishment of Malaysia and its confrontation with Indonesia. After leaving the military, he made a name for himself as a respected corporate leader. In particular, his contribution in taking charge of Sukom 98 and was given the mandate to lead companies like PERNAMA, AJINOMOTO and Country Heights Holdings.